Nutrition in Health and Disease - Our Challenges Now and Forthcoming Time 2019
DOI: 10.5772/intechopen.84467
|View full text |Cite
|
Sign up to set email alerts
|

Sports Nutrition and Performance

Abstract: Nutrition plays an essential role on sports performance. Following an adequate nutrition pattern determines winning the gold medal or failing in the attempt. That is why it is commonly referred to as "invisible training." However, regarding food and performance, it is not only referred to professional athletes. Nowadays, a large number of amateur athletes perform daily physical activity both recreationally and semiprofessionally. That population also seeks to achieve an improvement in their personal brands, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 38 publications
0
2
0
10
Order By: Relevance
“…Bireysel farklılıklar ve mevcut farklı yiyecek seçenekleri nedeniyle, sporcular için tek bir beslenme modeli yoktur, hatta değerlendirilecek çok sayıda strateji ve seçenek vardır (Saura, 2019). Estetik performans gerektiren spor dallarında (özellikle jimnastik, bale vb.)…”
Section: Kavramsal çErçeveunclassified
See 2 more Smart Citations
“…Bireysel farklılıklar ve mevcut farklı yiyecek seçenekleri nedeniyle, sporcular için tek bir beslenme modeli yoktur, hatta değerlendirilecek çok sayıda strateji ve seçenek vardır (Saura, 2019). Estetik performans gerektiren spor dallarında (özellikle jimnastik, bale vb.)…”
Section: Kavramsal çErçeveunclassified
“…Büyüme ve gelişmeyi sağlamak ve spor verimini arttırmak için beslenmenin türü ve niteliği oldukça önemlidir (Altundağ ve Payas, 2021: 116). Sporcu beslenme şekli, bireysel farklılıklara, yaptığı spor branşına, spor yapma süresine ve vücudun gereksinimine göre farklılık gösterir (Saura, 2019;Keser ve Yüksel, 2020). Fiziksel aktivite, atletik performans ve egzersiz sonrası toparlanma durumu optimal beslenme ile artar (Torres-McGehee vd., 2012).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Today, the evolution of football has shown that the nutritional preparation of the athlete is associated with the optimization of performance. However, a balanced and adequate diet provides energy substrates likely to improve the aerobic and anaerobic capacity of the player, which allows him to stay in the game for a long time [7]. It is therefore necessary to make the different foods known or within reach of the players while indicating their nutritional values.…”
Section: Problemmentioning
confidence: 99%
“…One can easily understand the existence of a good physical, mental, technical and nutrition [6]. It is therefore very important for an athlete to have notions of nutrition in order to know the quality and quantity of foods that are suitable for the energy needs of the activity [7]. The author stipulates that: "all players must choose their foods knowingly and according to the objectives they wish to achieve".…”
Section: Introductionmentioning
confidence: 99%